Bone and joint symptoms in Paget's disease. Issue 6 (December 1984) - Winfield, J; Stamp, T C
Abstract : Fifty patients with Paget's disease of bone were reviewed with regard to the basis of their symptoms and the long-term results of treatment. Twenty-four patients (48%) presented with pain localised within bone, while 17 (34%) presented with symptoms of degenerative joint disease. Three patients presented with bone pain and arthritis and the remaining six with fractures, ataxia, or painless deformity. Symptomatic osteoarthritis of the hip (OA) developed in 25 patients (50%) with approximately half developing radiological changes identical to those of idiopathic OA. Among the other patients those with coxa vara tended to show medial (rather than superior) joint space narrowing and severe Paget's disease on both sides of the joint. Arthritic pain, stiffness, and reduced mobility in other joints (knee, ankle, and wrist) were associated clinically with bone deformity adjacent to the affected joint and radiologically with distorted articular surfaces and narrowed joint spaces; sclerosis, subarticular cyst formation, and osteophytosis were usually absent. Fifteen patients were treated with calcitonin for bone pain alone; all claimed long-term 'good to complete' relief. By contrast, none of the 14 with arthritic symptoms responded to calcitonin when assessed retrospectively. Results of surgical and other medical treatment were analysed. Careful clinical evaluation is a prerequisite for optimal treatment in Paget's disease.